Evaluation for Retinal Therapy for RPE65 Variation Assessed in hiPSC Retinal Pigment Epithelial Cells. (13th December 2021) - Nash, Benjamin M.; Loi, To Ha; Fernando, Milan; Sabri, Amin; Robinson, James; Cheng, Anson; Eamegdool, Steven S.; Farnsworth, Elizabeth; Bennetts, Bruce; Grigg, John R.; Chung, Seo-Kyung; Gonzalez-Cordero, Anai; et al.
Abstract : Human induced pluripotent stem cells (hiPSCs) generated from patients and the derivative retinal cells enable the investigation of pathological and novel variants in relevant cell populations. Biallelic pathogenic variants in RPE65 cause early-onset severe retinal dystrophy (EOSRD) or Leber congenital amaurosis (LCA). Increasingly, regulatory-approved in vivo RPE65 retinal gene replacement therapy is available for patients with these clinical features, but only if they have biallelic pathological variants and sufficient viable retinal cells. In our cohort of patients, we identified siblings with early-onset severe retinal degeneration where genomic studies revealed compound heterozygous variants in RPE65, one a known pathogenic missense variant and the other a novel synonymous variant of uncertain significance. The synonymous variant was suspected to affect RNA splicing. Since RPE65 is very poorly expressed in all tissues except the retinal pigment epithelium (RPE), we generated hiPSC-derived RPE cells from the parental carrier of the synonymous variant. Sequencing of RNA obtained from hiPSC-RPE cells demonstrated heterozygous skipping of RPE65 exon 2 and the introduction of a premature stop codon in the mRNA. Minigene studies confirmed the splicing aberration. Results from this study led to reclassification of the synonymous variant to a pathogenic variant, providing the affected patients with access to RPE65 gene replacement therapy.